Homilie podczas Mszy św. w domu chorego, umierającego - Krzysteczko, Henryk (Studia Pastoralne, 2026)
Accompanying a terminally ill patient by celebrating Mass at home for him/her and his/her family gives a perfect opportunity to intensify one’s faith and to reflect on the importance of faith in life. It is also a chance to reconcile with God and the people as well as to accept sufferings and to offer them to God as a sacrifice for one’s own redemption, redemption of the family members, the Holy Church and all the people. The day’s readingcan be a good inspiration for homilies during Mass since they help to get a better understanding of the mystery of the Passion of Christ and Resurrection of Christ. The Eucharist which is the meeting with Christ enables the terminally ill patient to comprehend better the meaning of his/her life, suffering and death; thus he/she is well ‘equipped’ to bear the sufferings and to live the last moments of life in unity with God, being His witness at the same time. The family members of the terminally ill patient benefit from taking part in Mass as well because their faith becomes more intense and mature, the family bonds get stronger and so they are able to help their terminally ill next of kin to pass away to eternity. The work and assistance of doctors, nurses and volunteers who work in hospices is also of great importance because they take very good care of the terminally ill patients and their families. Homilies which were given by the writer of this paper during Masses celebrated at home for the terminally ill patients have been presented in this study. They covered the period of time starting from Ascension Day till the Day of Nativity of John Baptist – on Sundays, on days of special celebrations and church holidays.